2015
DOI: 10.1371/journal.pone.0142585
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Differentiation between Waxy and Common Maize by SNP Genotyping

Abstract: Waxy maize (Zea mays L. var. ceratina) is an important vegetable and economic crop that is thought to have originated from cultivated flint maize and most recently underwent divergence from common maize. In this study, a total of 110 waxy and 110 common maize inbred lines were genotyped with 3072 SNPs to evaluate the genetic diversity, population structure, and linkage disequilibrium decay as well as identify putative loci that are under positive selection. The results revealed abundant genetic diversity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
(64 reference statements)
1
11
0
1
Order By: Relevance
“…Based on its LD value, potato behaves as a self-pollinated crop even if it is an outcrossing species. The clonal propagation of potato limits the number of meiotic generations and in consequence the recombination events [ 33 35 , 118 ]. The LD in Andigena and Phureja decayed slowly, previous works also reported a slow LD decay for potato populations: 1 cM [ 33 ], 10 cM [ 35 ] and 5 cM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on its LD value, potato behaves as a self-pollinated crop even if it is an outcrossing species. The clonal propagation of potato limits the number of meiotic generations and in consequence the recombination events [ 33 35 , 118 ]. The LD in Andigena and Phureja decayed slowly, previous works also reported a slow LD decay for potato populations: 1 cM [ 33 ], 10 cM [ 35 ] and 5 cM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean PIC of markers present within wx1 locus is lower than PIC of genome-based SSRs observed in waxy germplasm. For example, Hung et al (2012) and Hao et al (2015) reported PIC of 0.46 and 0.31 in waxy germplasm, respectively. The higher PIC values, 0.70 and 0.62 among waxy maize germplasm were observed by Zheng et al (2013) and Sa et al (2015), respectively.…”
Section: Genetic Variation In Wx1 Locusmentioning
confidence: 99%
“…In contrast, Sa et al (2015) reported higher number of alleles [1268 alleles, 6.34 average alleles/locus and 2-14 alleles/locus] among 40 waxy inbreds of South Korea using 200 SSRs. Further, Hao et al (2015) analysed 110 waxy maize accessions using 2751 single nucleotide polymorphisms (SNPs) and detected two alleles/locus. In the present study, allele size ranged from 60 bp (phi028) to 300 bp (bnlg1635 and phi113) across markers, which revealed the presence of high genetic diversity of the loci analysed.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…The germplasm base of waxy corn is narrow compared to normal maize, as few countries have active waxy corn breeding programme. Only few reports from China (Yu et al 2012;Zheng et al 2013;Hao et al 2015), Vietnam (Liet and Tinh 2009;Hung et al 2012) and Korea (Park et al 2008;Sa et al 2015) are available on molecular characterization of waxy inbreds. In India, so far waxy trait has not been utilized in the breeding programme, despite the fact that people in north-eastern states of the country prefers waxy maize as a food over traditional maize.…”
Section: Introductionmentioning
confidence: 99%